An Example of Ketone Olefination via Praseodymium-Mediated Barbier Reaction in the Presence of Diethyl Phosphite - Cao, Xu yan; Huang, Fei; Zhang, Songlin (Synlett, 2019)
The first example of carbon double-bond formation via praseodymium-mediated Barbier type reaction of ketones and allyl halides in the presence of diethyl phosphite is reported. The reaction is highly α-regioselective and conveniently carried out under mild conditions in a one-pot fashion. From a synthetic point of view, a series of conjugated alkenes were obtained in moderate to good yields in this one-pot reaction with practical reaction conditions.
Keywords: Barbier type reaction; ketones; diethyl phosphite; α-regioselective; conjugated alkenes